"KNOWLEDGE AND ATTITUDE ABOUT ADVERSE DRUG REACTION REPORTING AMONG DOCTORS AT A TERTIARY CARE HOSPITAL" - SATHISHA AITHAL; TANUJA V HOOLI; VARUN HV (International Journal of Pharma and Bio Sciences, 2014)
Adverse drug reactions are responsible for mortality and morbidity during medical care. Spontaneous reporting of adverse drug reaction from treating physician plays an important role in assessing the benefit and risk profile of marketed drugs periodically.To assess the knowledge and attitude about adverse drug reaction reporting among the health care professionals working in a tertiary care hospital. This was a cross- sectional study conducted on doctors working at a tertiary care hospital using a standardized questionnaire. The participants were enrolled in the study after obtaining informed consent.Forty two doctors (N=42) agreed to participate in the study. Around 38% of responders were aware of adverse drug reaction reporting centre in their institution. 26% of participants were aware of essential factors required for reporting of an ADR and also knew that causality assessment is not a must for reporting. The most common factors for discouraging reporting of adverse drug reaction was non- availability of reporting forms (47%) followed by lack of time (42%).The most common factors encouraging reporting of an adverse drug reaction included seriousness of the event (95%). The average scores of all participants for attitude related questions were approximately 76(maximum score 115). There was no significant difference in attitude scores between gender, and between cadre level (P>0.05).The result of the present study indicates that there is a need to create awareness about adverse drug reaction reporting among doctors. The factors discouraging reporting of an adverse drug reaction could be addressed by the local adverse drug reaction reporting centre.